2015
DOI: 10.1007/s00262-015-1720-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell immunosenescence in acute myeloid leukaemia patients: new targets for immunotherapeutic strategies?

Abstract: Several age-associated changes in natural killer (NK) cell phenotype have been reported that contribute to the defective NK cell response observed in elderly patients. A remodelling of the NK cell compartment occurs in the elderly with a reduction in the output of immature CD56(bright) cells and an accumulation of highly differentiated CD56(dim) NK cells. Acute myeloid leukaemia (AML) is generally a disease of older adults. NK cells in AML patients show diminished expression of several activating receptors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 87 publications
(157 reference statements)
3
32
0
1
Order By: Relevance
“…Overall, this study confirmed, as expected, the phenotypic characteristics of CD56 bright NK cells (1). It is known that the percentages and absolute numbers of NK cells increase in healthy ageing, but the decrease in the CD56 bright subset is interpreted as a lower output of such NK cells from the bone marrow (21).…”
Section: Cd56supporting
confidence: 74%
“…Overall, this study confirmed, as expected, the phenotypic characteristics of CD56 bright NK cells (1). It is known that the percentages and absolute numbers of NK cells increase in healthy ageing, but the decrease in the CD56 bright subset is interpreted as a lower output of such NK cells from the bone marrow (21).…”
Section: Cd56supporting
confidence: 74%
“…These false negative cases strongly suggest that additional parameters are involved in relapse. The immune landscape of tumors is obviously more complex, [ 52 ] and beside alterations of NCR, additional anomalies have been described on both NK cell [ 53 55 ] and T cell subsets [ 56 , 57 ]. Clinical consequences of such immune profiles remain to be tested or validated.…”
Section: Discussionmentioning
confidence: 99%
“…Se sabe que el comportamiento de determinados tumores sufre alteraciones con la edad, presentando signos clínicos más agresivos por medio de alteraciones en su genoma, debido a la preparación menos eficiente del ácido desoxirribonucleico (ADN), edad biológica del tumor, sistema inmunológico comprometido, aumento de la carcinogénesis por influencia de la inflamación sistémica o resistencia a quimioterápicos 10 .…”
Section: Programa De Residencia En Nutrición Clínica En El Hospital unclassified